A novel near-infrared fluorescent light-up probe for tumor imaging and drug-induced liver injury detection. Issue 17 (11th February 2019) - Zeng, Xiaodong; Chen, Ziyang; Tang, Lin; Yang, Han; Liu, Nan; Zhou, Hui; Li, Yang; Wu, Junzhu; Deng, Zixin; Yu, Yi; Deng, Hai; Hong, Xuechuan; et al.
Abstract : A novel light-up NIR fluorescence probe was developed and used for tumor and drug-induced liver injury imaging in vivo . Abstract : A novel near-infrared fluorescent light-up probe with a tumor-homing pentapeptide, CREKA (Cys-Arg-Glu-Lys-Ala), specifically binds to fibrin–fibronectin complexes was rationally designed and developed for biomedical imaging. Its superior practical applications in tumor imaging and drug-induced liver injury detection are well demonstrated for the first time.